2005
DOI: 10.1089/oli.2005.15.206
|View full text |Cite
|
Sign up to set email alerts
|

518A2 Melanoma Cells Are Protected by G3139 and Other Antineoplastic Agents Against the Cytotoxic Effects of DTIC

Abstract: G3139 is an antisense Bcl-2 phosphorothioate oligonucleotide that has been combined with DTIC in a phase III clinical trial in melanoma. However, its actual mechanism of action in melanoma is controversial. Treatment of 518A2 melanoma cells with either G3139 or G4126 (a two-base mismatch) and then with light-activated DTIC caused these cells (but not SK-Mel-30 or 346.1 cells) to be protected against the cytotoxic effects of DTIC. This cytoprotection was not recapitulated with a phosphodiester congener of G3139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Numerous laboratory studies appear to provide circumstantial evidence for this speculation, as it has been shown that some mechanisms of resistance are operational in mediating resistance to DTIC [18] . Benimetskaya et al [19] recently reported that treatment of 518A2 melanoma cells with agents such as Bcl-2 antisense, cisplatin or gemcitabine induced cytoprotection to DTIC. It is tempting to conclude that cytoprotection to DTIC is a stress response to chemical proapoptotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous laboratory studies appear to provide circumstantial evidence for this speculation, as it has been shown that some mechanisms of resistance are operational in mediating resistance to DTIC [18] . Benimetskaya et al [19] recently reported that treatment of 518A2 melanoma cells with agents such as Bcl-2 antisense, cisplatin or gemcitabine induced cytoprotection to DTIC. It is tempting to conclude that cytoprotection to DTIC is a stress response to chemical proapoptotic stress.…”
Section: Discussionmentioning
confidence: 99%